Establishing Chemical Management Network in the East of Thailand by Participation Process - รักษาคม, หรรษา; ศรีประพัฒน์, พูนศักดิ์; ปัทเมฆ, ชะฎายุทธ์ (Disease Control Journal, 2010)
Based on Participatory Action Research, this Research and Development comprised of 3 steps: 1) Preparing and planning 2) Action and 3) Evaluation. Its objective was to establish the chemical management network in the East of Thailand by participation process among organizations in governmental and private sectors. Purposive samples included voluntary officers responsible for chemical management in 2 provinces (Chonburi and Rayong). Data collection during April 2006 - October 2007 was obtained through activity record and evaluation of participation behavior. Descriptive analysis was presented in percentage. The products of the 1st step included conceptual framework and 4 steps of network activities with 5 activities. The 2nd step involved 38 organizations in the workshop and production of manuals for the personnel and the public. Participation building processes such as AIC (Appreciate Influence Control) and FSC (Future Search Conference) technic were applied in the workshop with 93% and 7% of network members at high and middle level of network participation, respectively. For the manual production, 82.6% and 17.4% of the members were at high and middle level of participation, respectively. The 3rd step indicated that the input and the process were good, activities were performed as planned, and the activities were useful and suitable for the problems in the area. In conclusion, the chemical management network in the East of Thailand was built up through the participation process driven by network activities. The key success factors included network coordination, regular activities, network outputs with shared benefits; whereas personnel change and interruption of some activities were main obstacles. The network sustainability, public participation, and application for other public health problems were suggested for the next steps of development.